Aqueous humor ferritin in hereditary hyperferritinemia cataract syndrome - Lenzhofer, Markus; Schroedl, Falk; Trost, Andrea; Kaser-Eichberger, Alexandra; Wiedemann, Helmut; Strohmaier, Clemens; Hohensinn, Melchior; Strasser, Michael; Muckenthaler, Martina; Grabner, Guenther; Aigner, Elmar; Reitsamer, Herbert A. (Optometry and vision science, 2015)
Hereditary hyperferritinemia cataract syndrome (HHCS) is a rare autosomal dominant hereditary disease, characterized by hyperferritinemia but with absence of body iron excess and early onset of bilateral cataracts. Although 5- to 20-fold increased serum ferritin concentrations have been reported in HHCS patients, data of ferritin levels in aqueous humor have not been obtained. We therefore aimed to investigate the ferritin levels in aqueous humor and serum and further present histological and ultrastructural data of the lens.
Gesehen am 17.06.2020